Feasibility study of GaN-based MEMS capacitive microphone using finite element method - Rahmat Zaki Auliya,; M. F. Mohd. Razip Wee,; Subandi, Ayub; Muhammad Ramdzan Buyong,; Burhanuddin Yeop Majlis, (Penerbit Universiti Kebangsaan Malaysia, 2020)
Gallium nitride (GaN) is an excellent choice of semiconductor material due to its optoelectronic, mechanical and wide bandgap properties which are highly demanded by high-power and radio-frequency (RF) electronics but also widely employed for the fabrication of Light Emitting Diode (LED). In this paper, we explored the advantage of GaN as an electromechanical material to be used in microelectromechanical systems (MEMS) microphone as a thin film membrane through a theoretical study performed using the finite element method. We consider also the anisotropy and symmetry structural of GaN to be employed as microphone membrane. In addition, we compared also its performance in terms of sensitivity, C-V measurement and pull-in voltage with several conventional membrane materials such as silicon, nickel, and silicon nitride. The result shows that GaN-based MEMS capacitive microphone has sensitivity -57 dBV/Pa which is 4% higher than silicon nitride-based microphone and resonance frequency of 19 kHz which is higher 11.3% than nickel-based microphone. Hence, this theoretical study could pave a way for GaN to be developed especially for MEMS microphone applications and boasted also by the recent advancement of GaN related fabrication. The advantages of GaN compared to other conventional semiconductor material could be useful for the development of ultrasonic MEMS microphone for utilize detection of sound beyond audible frequency range.